AKUNTABILITAS DAN TRANSPARANSI ANGGARAN PEMERINTAH SEBELUM DAN SAAT COVID-19 PADA WEBSITE PEMDA DI KAWASAN INDONESIA TIMUR - Umasangaji, Imam Osama (Jurnal Pelita Ilmu, 2024)
This research aims to find out how the accountability and transparency of government budgets differ before and during Covid-19 on regional government websites in the Eastern Indonesia region. This research uses content analysis using indicators to measure the implementation of accountability and transparency on regional government websites in the Eastern Indonesia region, while the data collection method uses the documentation method. The collected data was then carried out with a Wilcoxon single rank test using SPSS to find out whether there were differences in the level of accountability and transparency on regional government websites in the Eastern Indonesia region. The results of the research conducted show that there are differences in the value of accountability and transparency of the Government budget before and during Covid-19 on regional government websites in the Eastern Indonesia region. The value shows that the provincial average has increased quite significantly, this can be seen from the increasingly complete budget reports published on the regional government website in the three years since the Covid-19 pandemic was declared. However, there are also provinces that actually experience a decrease in value because the published budget reports are less complete than before the Covid-19 pandemic.